How to Find Medical Information on the Internet: A Print and Online Tutorial for the Healthcare Professional and Consumer - Debbie Jan (Issues in Science and Technology Librarianship)
The article reviews the book How to Find Medical Information on the Internet: A Print and Online Tutorial for the Healthcare Professional and Consumer. Berkeley, CA: Library Solutions Press, 2000. Internet Workshop Series No. 10. 128p. $60.00. (ISBN 1-882208-27-7) by Diane K. Kovacs and Ann L. Carlson.